Dynamic response of magnetic nanoparticles arranged in a tubular shape - Curiale, Carlos Javier; Sanchez, Rodolfo Daniel; Ramos, Carlos Alberto; Leyva de Guglielmino, Ana Gabriela; Butera, Alejandro Ricardo (Elsevier Science, 2008)
Fil: Curiale, Carlos Javier. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina